Multi-Objective Optimization of the Pasteurization Process of Pumpkin Cubes Packaged in Glass Jars - Lespinard, Alejandro Rafael (2015)
The influence of particle size (PZ) and processing temperature (PT) on quality attributes and processing time of pumpkin cubes packaged in glass jars were evaluated during their pasteurization. Second-order polynomial models were developed for the following responses: texture retention (TR), total colour change (TCC) and heating time (HT), using multiple linear regression for a range of operating conditions (20-30 mm and 85-100°C for PZ and PT, respectively). A combination of the polynomial models with the methodology of desirability function was used for optimization of the pumpkin pasteurization process. The obtained optimal conditions were 20 mm and 100°C for PZ and PT, respectively; in order to obtain TR of 82.21%, TCC of 7.54 and HT of 44.97 min. However, these optimal conditions change to 100°C and 21 mm and the responses obtained are TR of 73.60%, TCC of 7.52 and HT of 39.66 min, when the processing time is prioritized.